Knowledge of the Saudi hypertensive individuals towards hypertension: a cross-sectional analytical study - Al-Shehri, Hamdan M. (International Journal Of Community Medicine And Public Health, 2023)
Background: This cross-sectional study aimed to assess the knowledge of hypertension among adults living in Saudi Arabia. This information will be valuable for healthcare providers, public health organizations, and policy makers in developing effective health education programs and interventions to improve the management and prevention of hypertension in Saudi Arabia Methods: The study was conducted during the period from October 2022 to December 2022 and utilized an online survey with a sample size of 1234 adults with a minimum age of 18 years. The survey consisted of questions regarding sociodemographic characteristics and knowledge of hypertension, including causes, symptoms, risk factors, and management. Results: The results showed that most participants had a general understanding of hypertension, with the majority (79.7%) knowing the normal values of blood pressure and 63.7% understanding that it is a treatable condition. The most common source of knowledge about hypertension was through friends and family (53.1%). Conclusions: The study highlights the need for continued education and awareness about hypertension in Saudi Arabia, particularly for those with limited education and older individuals.